CONCEPT OF LITHUANIAN LANGUAGE AND LITERATURE: A DISCOURSE ON DEVELOPMENT OF SECONDARY EDUCATION - Nauckūnaitė, Zita (Acta Paedagogica Vilnensia, 2011)
The article analyzes gradual change of the concept of Lithuanian Language and Literature as a school subject in general education from 1993 to 2011. It focuses on secondary education defined by General Curriculum Framework for secondary education and Examination Syllabus. The latter has been serving as a source of orientation for teachers of 11th – 12th forms. Since compulsory matura examination has a strong washback effect on the whole process of education, a detailed analysis of the examination tasks is presented. The principal proposition is that the tasks have been far from appropriate: the test on understanding a text is of low discriminating value, it distorts the natural process of reading, since the reader does not put forward personal hypotheses, as it happens in natural reading, but has to rely on the hypotheses suggested by the tester’s questions, therefore reading loses its authenticity; analysis and interpretation of a piece of fiction is not appropriate as an examination task because of its framework of assessment, which inevitably becomes a landmark of literary education and, while focusing student’s attention on a separate fragment, separates the student from authentic perception of a literary work, holds back the development of powerful thinking, fosters a fragmented noncommittal personality. The conclusion states that the matura examination of Lithuanian language and literature should be designed with the positive washback in view. The following aims of the 2013 examination on Lithuanian language and literature are presented: to assess students’ general literacy, i.e. the ability to write a cohesive argumentative text meeting the language requirements of accuracy; to assess students’ general abilities to solve problems, analyze, make interpretations and evaluations. Two genres suggested for matura examination are discussed: an essay for analysis of literary works chosen from the syllabus, and argumentative composition for discussing cultural and everyday life issues in an appropriate context and with the reference to at least one piece of literature.